Inhibitory Effect of Cinnamaldehyde, Citral, and Eugenol on Aflatoxin Biosynthetic Gene Expression and Aflatoxin B1 Biosynthesis in Aspergillus flavus. Issue 12 (10th November 2015) - Liang, Dandan; Xing, Fuguo; Selvaraj, Jonathan Nimal; Liu, Xiao; Wang, Limin; Hua, Huijuan; Zhou, Lu; Zhao, Yueju; Wang, Yan; Liu, Yang
Abstract: In order to reveal the inhibitory effects of cinnamaldehyde, citral, and eugenol on aflatoxin biosynthesis, the expression levels of 5 key aflatoxin biosynthetic genes were evaluated by real‐time PCR. Aspergillus flavus growth and AFB1 production were completely inhibited by 0.80 mmol/L of cinnamaldehyde and 2.80 mmol/L of citral. However, at lower concentration, cinnamaldehyde (0.40 mmol/L), eugenol (0.80 mmol/L), and citral (0.56 mmol/L) significantly reduced AFB1 production with inhibition rate of 68.9%, 95.4%, and 41.8%, respectively, while no effect on fungal growth. Real‐time PCR showed that the expressions of aflR, aflT, aflD, aflM, and aflP were down‐regulated by cinnamaldehyde (0.40 mmol/L), eugenol (0.80 mmol/L), and citral (0.56 mmol/L). In the presence of cinnamaldehyde, AflM was highly down‐regulated (average of 5963 folds), followed by aflP, aflR, aflD, and aflT with the average folds of 55, 18, 6.5, and 5.8, respectively. With 0.80 mmol/L of eugenol, aflP was highly down‐regulated (average of 2061‐folds), followed by aflM, aflR, aflD, and aflT with average of 138‐, 15‐, 5.2‐, and 4.8‐folds reduction, respectively. With 0.56 mmol/L of citral, a flT was completely inhibited, followed by aflM, aflP, aflR, and aflD with average of 257‐, 29‐, 3.5‐, and 2.5‐folds reduction, respectively. These results suggest that the reduction in AFB1 production by cinnamaldehyde, eugenol, and citral at low concentration may be due to the down‐regulations of the transcription level of aflatoxin biosynthetic genes. Cinnamaldehyde and eugenol may be employed successfully as a good candidate in controlling of toxigenic fungi and subsequently contamination with aflatoxins in practice.